Phytotherapy of experimental depression: Kalanchoe integra Var. Crenata (Andr.) Cuf Leaf Extract - Kennedy K E Kukuia; Isaac J Asiedu-Gyekye; Eric Woode; Robert P Biney; Emmanuel Addae (Wolters Kluwer Medknow Publications, 2015)
Context: Kalanchoe sp. have been used since 1921 for central nervous system (CNS) disorders such as psychosis and depression. It is known to possess CNS depressant effects. Aims: To investigate the antidepressant properties of the aqueous leaf extract of Kalanchoe integra. Settings and Design: The study was carried out at the Kwame Nkrumah University of Science and Technology between 6 a.m. and 3 p.m. Materials and Methods: ICR mice were subjected to the forced swimming test (FST) and tail suspension test (TST) after they had received extract (30-300 mg/kg), fluoxetine (3-30 mg/kg), desipramine (3-30 mg/kg) orally, or water (as vehicle). In a separate experiment, mice were pre-treated with reserpine (1 mg/kg), α-methyl paratyrosine (AMPT; 400 mg/kg), both reserpine (1 mg/kg) and AMPT (200 mg/kg) concomitantly, or p-chlorophenylalanine (pCPA; 200 mg/kg) to ascertain the role of the noradrenergic and serotoninergic systems in the mode of action of the extract. Statistical analysis used: Means were analyzed by analysis of variance (ANOVA) followed by Newman-Keuls' post hoc test. P < 0.05 was considered significant. Results: In both FST and TST, the extract induced a decline in immobility, indicative of antidepressant-like effect. This diminution in immobility was reversed by pCPA, but not by reserpine and/or AMPT. The extract increased the swimming and climbing scores in the FST, suggestive of possible interaction with serotoninergic and noradrenergic systems. In the TST, the extract produced increases in both curling and swinging scores, suggestive of opioidergic monoaminergic activity, respectively. Conclusions: The present study has demonstrated the antidepressant potential of the aqueous leaf extract of K. integra is mediated possibly by a complex interplay between serotoninergic, opioidergic, and noradrenergic systems.